Evaluation of the Inductive Coupling between Equivalent Emission Sources of Components - Moisés Ferber; Sanâa Zangui; Carlos Sartori; Christian Vollaire; Ronan Perrussel; Laurent Krähenbühl (International Journal of Antennas and Propagation)
The electromagnetic interference between electronic systems or between their components influences the overall performance. It is important thus to model these interferences in order to optimize the position of the components of an electronic system. In this paper, a methodology to construct the equivalent model of magnetic field sources is proposed. It is based on the multipole expansion, and it represents the radiated emission of generic structures in a spherical reference frame. Experimental results for different kinds of sources are presented illustrating our method.